From ponds to plates: the role of crop-aquaculture farming systems in building household food security in Myanmar - Kotchofa, Pacem; Buisson, Marie-Charlotte; Win, Shelly (2025)
While Myanmar’s agricultural sector faces significant challenges, including water scarcity, inefficient resource use, and low agricultural productivity, integrated food systems, such as Crop and Aquaculture Farming (CAF) systems, offer a potential pathway to alleviate these challenges by creating a synergetic environment where crops and aquaculture can thrive. At the same time, it also enhances environmental sustainability, economic resilience, and household food and nutrition outcomes. This study evaluates the impact of CAF on food security and explores its adoption among vulnerable farming households in Myanmar. We use two data sources: the Myanmar Household Welfare Survey collected by IFPRI and secondary data from the Aquaculture Suitability Decision Support Tool (Aqua-DST), which covers he Upper Ayeyarwady river basins in Myanmar. We modeled logit and propensity score matching (PSM) regressions to assess the relationship between CAF adoption and household food insecurity (FI).